2021
DOI: 10.1039/d1sm00451d
|View full text |Cite
|
Sign up to set email alerts
|

Predicting human touch sensitivity to single atom substitutions in surface monolayers for molecular control in tactile interfaces

Abstract: The mechanical stimuli generated as a finger interrogates the physical and chemical features of an object forms the basis of fine touch. Haptic devices, which are used to control touch,...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 63 publications
0
26
1
Order By: Relevance
“…Hysteresis was calculated by taking the difference of each advancing and receding angle pair. 15 We reported the average receding angle, average advancing angle, and standard deviation of the hysteresis.…”
Section: Experimental Methods and Rationalementioning
confidence: 99%
See 3 more Smart Citations
“…Hysteresis was calculated by taking the difference of each advancing and receding angle pair. 15 We reported the average receding angle, average advancing angle, and standard deviation of the hysteresis.…”
Section: Experimental Methods and Rationalementioning
confidence: 99%
“…The challenge of connecting molecular scale effects with human performance is the inability to sufficiently describe friction with simple material properties such as a constant coefficient of friction, the human variability in applied force and sliding velocity, the contact mechanics of the finger, and the lack of established relationships between friction and tactile percepts. 15–17…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aristotle's observation that the human hand is the "tool of tools" pays homage to its functionality. Recent studies have demonstrated that our fingertips can detect differences in surfaces altered at the molecular level (Nolin et al, 2021). Reaching out to grasp a coffee cup, manipulating the button of a shirt, or pinching a minute quantity of salt while cooking are difficult tasks to replicate with present day robotic systems.…”
Section: The Ramifications Of Hand Lossmentioning
confidence: 99%